Reversal in the relative performance of state- and legal person-owned companies during the Chinese split share structure reform - Vong, A. P. I.; Trigueiros, D. (Applied Economics, 2014)
The split share structure reform was started in 2005 with the object of re-designating state-related, nontradable shares into tradable shares. The article compares the two major forms of state ownership in China (direct or indirect ownership) showing that, close to the reform period, companies directly held by the state experience a significant increase in market performance relative to indirectly held companies. Results suggest that investors' perception about the worth of these two forms of state ownership may have suffered a reversal, thus bringing to light value-related consequences ensuing from protective schemes usual in China and elsewhere. The article also addresses a recurrent pitfall relating to the use in empirical models of fractions of the same total and shows that U-shaped patterns found in the relationship between ownership and performance are transient rather than stable.